FAKTOR-FAKTOR YANG MEMENGARUHI HALAL AWARENESS PELAKU USAHA PANGAN DI PULAU MADURA - Risma Evinda Yuleha; Mochamad Reza Adiyanto (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted to determine the level of halal awareness of food business owners on Madura Island. The approach used is quantitative, and data collection is done by distributing questionnaires and interviews. Determination of the sample using probability sampling in which all business owners have the opportunity to be selected as the research sample. The respondents were 100 people. The data analysis technique uses descriptive analysis to describe the length of the business and monthly income. Data testing uses IBM SPSS Statistics 25 to test the independent variables on the dependent variable. Most business owners have run their businesses for under five years, and their monthly income is below IDR 5,000,000. The level of awareness of food business owners on Madura Island is as much as 98% of food business owners understand halal certification. Simultaneously worship activities, beliefs about halal food, knowledge about halal food, health reasons, and halal labels affect halal awareness of food business actors on Madura Island, where halal awareness of food business actors can be explained by the variables of worship activity, beliefs about halal food, knowledge about halal food, health reasons, and halal labels is 51.9%. At the same time, the rest is influenced by other factors outside of the research. Religious activities, knowledge of halal food, and halal labels significantly affect halal awareness, while health reasons have an effect but not significantly. Meanwhile, beliefs about halal food did not significantly affect halal awareness.